2013
DOI: 10.1016/j.rmed.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambulatory oxygen on exertional dyspnea in IPF patients without resting hypoxemia

Abstract: Since oxygen provides no additional benefit over air in terms of exertional dyspnea for IPF patients without resting hypoxemia, routine prescription of ambulatory oxygen is not recommended. However, assessment on an individual basis is necessary. Trial registration. UMIN Clinical Trial Registry; No.:UMIN000005098; URL:http://www.umin.ac.jp/ctr/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 29 publications
1
68
1
6
Order By: Relevance
“…−0.37 (95% CI −0.50-−0.24) [164]. In patients with ILD, also dyspnoeic at rest, the effects of ambulatory oxygen therapy on dyspnoea (CR-10) in hypoxaemic [165] and nonhypoxaemic subjects parallel those described for COPD [166].…”
Section: Discussionmentioning
confidence: 71%
“…−0.37 (95% CI −0.50-−0.24) [164]. In patients with ILD, also dyspnoeic at rest, the effects of ambulatory oxygen therapy on dyspnoea (CR-10) in hypoxaemic [165] and nonhypoxaemic subjects parallel those described for COPD [166].…”
Section: Discussionmentioning
confidence: 71%
“…Whether the effect of oxygen therapy is related to a placebo effect remains subject to debate. In a controlled study, supplemental oxygen given at exercise in IPF patients with exertional arterial hypoxaemia but without resting arterial hypoxaemia failed to improve the 6-min walk distance and dyspnoea in comparison with placebo (air), despite improvements in arterial haemoglobin saturation [133], while another study reported beneficial effects with regard to endurance time and dyspnoea [134]. Indirect evidence suggests key roles of dead space ventilation in the genesis of dyspnoea, although the lack of a possibility to experimentally amend the VD/VT ratio precludes definitive demonstration.…”
Section: How Do Physiological Alterations Integrate In Ipf? Exercise mentioning
confidence: 95%
“…1 Currently, there are no randomised controlled trials to demonstrate that ambulatory oxygen therapy is effective in achieving these aims in patients with IPF, thus, assessment on an individual basis is necessary. 17 The thorax survey suggested significant support for ambulatory oxygen therapy, but variation when it was offered to patients. A 6 min walk or shuttle walk test will provide the most accurate indication of exercise-induced desaturation and the required level of oxygen supplementation.…”
Section: Ambulatory Oxygenmentioning
confidence: 99%